Biofilm enrichment of spray-paint endemic microbial communities suitable for graffiti bioremoval - Cristina Cattò; Patricia Sanmartín; Francesca Cappitelli (International Biodeterioration & Biodegradation, 2026)

Pollution gradients shape structure and functions of stone heritage bacterial communities at global scale - Haiqing Yang; Francesca Cappitelli; Xingyue Li (Science of The Total Environment, 2025)

Methodological challenges for the investigation of the dual role of biofilms on outdoor heritage - Letizia Berti; Federica Villa; Lucia Toniolo; Francesca Cappitelli; Sara Goidanich (Science of The Total Environment, 2024)

Ecological strategies of bacterial communities in prehistoric stone wall paintings across weathering gradients: A case study from the Borana zone in southern Ethiopia - Gianmarco Mugnai; Luigimaria Borruso; Ying-Li Wu; Marina Gallinaro; Francesca Cappitelli; Andrea Zerboni; Federica Villa (Science of The Total Environment, 2024)

Biofilm colonization of stone materials from an Australian outdoor sculpture: Importance of geometry and exposure - Cristina Cattò; Andre Mu; John W. Moreau; Nancy Wang; Francesca Cappitelli; Richard Strugnell (Journal of Environmental Management, 2023)

The response of Escherichia coli biofilm to salicylic acid - Cristina Cattò; Giovanni Grazioso; Silvia Dell’Orto; Arianna Gelain; Stefania Villa; Valeria Marzano; Alberto Vitali; Federica Villa; Francesca Cappitelli; Fabio Forlani (Biofouling, 2017)

Coating polypropylene surfaces with protease weakens the adhesion and increases the dispersion of Candida albicans cells - Eugenio Spadoni Andreani; Federica Villa; Francesca Cappitelli; Anna Krasowska; Piotr Biniarz; Marcin Łukaszewicz; Francesco Secundo (Biotechnology Letters, 2017)

Mini-review: Biofilm responses to oxidative stress - Michela Gambino; Francesca Cappitelli (Biofouling, 2016)

Immobilized Hydrolytic Enzymes Exhibit Antibiofilm Activity Against Escherichia coli at Sub-Lethal Concentrations - Federica Villa; Francesco Secundo; Andrea Polo; Francesca Cappitelli (Current Microbiology, 2015)

Assessing the microbiological risk to stored sixteenth century parchment manuscripts: a holistic approach based on molecular and environmental studies - Federica Troiano; Andrea Polo; Federica Villa; Francesca Cappitelli (Biofouling, 2014)

A simple and reliable methodology to detect egg white in art samples - Michela Gambino; Francesca Cappitelli; Cristina Cattò; Aristodemo Carpen; Pamela Principi; Lisa Ghezzi; Ilaria Bonaduce; Eugenio Galano; Pietro Pucci; Leila Birolo; Federica Villa; Fabio Forlani (Journal of Biosciences, 2013)

Plant-derived bioactive compounds at sub-lethal concentrations: towards smart biocide-free antibiofilm strategies - Federica Villa; Francesca Cappitelli (Phytochemistry Reviews, 2013)

Sub-lethal concentrations of Muscari comosum bulb extract suppress adhesion and induce detachment of sessile yeast cells - Federica Villa; Gigliola Borgonovo; Francesca Cappitelli; Barbara Giussani; Angela Bassoli (Biofouling, 2012)

Importance of subaerial biofilms and airborne microflora in the deterioration of stonework: a molecular study - Andrea Polo; Davide Gulotta; Nadia Santo; Cristiano Di Benedetto; Umberto Fascio; Lucia Toniolo; Federica Villa; Francesca Cappitelli (Biofouling, 2012)

Effects of chronic sub-lethal oxidative stress on biofilm formation by Azotobacter vinelandii - Federica Villa; William Remelli; Fabio Forlani; Michela Gambino; Paolo Landini; Francesca Cappitelli (Biofouling, 2012)

Altered expression level of Escherichia coli proteins in response to treatment with the antifouling agent zosteric acid sodium salt - Federica Villa; William Remelli; Fabio Forlani; Alberto Vitali; Francesca Cappitelli (Environmental Microbiology, 2012)
Summary Zosteric acid sodium salt is a powerful antifouling agent. However, the mode of its antifouling action has not yet been fully elucidated. Whole cell proteome of Escherichia coli was analysed to study the different protein patterns expressed by the surface‐exposed planktonic cells without and with sublethal concentrations of the zosteric acid sodium salt. Proteomic analysis revealed that at least 27 proteins showed a significant (19 upregulated and 8 downregulated, P E. coli cells, which favours the expression of various protective proteins, the AI‐2 production and the synthesis of flagella, to escape from adverse conditions.

Cyanobacteria cause black staining of the National Museum of the American Indian Building, Washington, DC, USA - Francesca Cappitelli; Ornella Salvadori; Domenico Albanese; Federica Villa; Claudia Sorlini (Biofouling, 2012)

Hindering biofilm formation with zosteric acid - Federica Villa; Domenico Albanese; Barbara Giussani; Philip S. Stewart; Daniele Daffonchio; Francesca Cappitelli (Biofouling, 2010)

N-vanillylnonanamide tested as a non-toxic antifoulant, applied to surfaces in a polyurethane coating - Federica Villa; Lucia Giacomucci; Andrea Polo; Pamela Principi; Lucia Toniolo; Marienella Levi; Stefano Turri; Francesca Cappitelli (Biotechnology Letters, 2009)

Chemical–physical and Microbiological Measurements for Indoor Air Quality Assessment at the Ca’ Granda Historical Archive, Milan (Italy) - Francesca Cappitelli; Paola Fermo; Roberta Vecchi; Andrea Piazzalunga; Gianluigi Valli; Elisabetta Zanardini; Claudia Sorlini (Water, Air, & Soil Pollution, 2009)